2008
DOI: 10.1289/ehp.10735
|View full text |Cite
|
Sign up to set email alerts
|

Residential Traffic and Children’s Respiratory Health

Abstract: BackgroundLiving near traffic has been associated with asthma and other respiratory symptoms. Most studies, however, have been conducted in areas with high background levels of ambient air pollution, making it challenging to isolate an independent effect of traffic. Additionally, most investigations have used surrogates of exposure, and few have measured traffic pollutants directly as part of the study.ObjectiveWe conducted a cross-sectional study of current asthma and other respiratory symptoms in children (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 24 publications
(56 reference statements)
1
73
0
3
Order By: Relevance
“…In most studies published after the 2009 EPA integrated science assessment, (total) organic carbon has been found to be associated with short-term changes in cardiovascular (Delfino et al, 2010a;Ito et al, 2011;Kim et al, 2012;Son et al, 2012;) and respiratory health (Kim et al, 2008), or with changes in the levels of inflammatory markers (Hildebrandt et al, 2009). …”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies published after the 2009 EPA integrated science assessment, (total) organic carbon has been found to be associated with short-term changes in cardiovascular (Delfino et al, 2010a;Ito et al, 2011;Kim et al, 2012;Son et al, 2012;) and respiratory health (Kim et al, 2008), or with changes in the levels of inflammatory markers (Hildebrandt et al, 2009). …”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Many studies have shown excess health risks in proximity to roads -after adjustment for a range of possible confounders, including socioeconomic status -for such outcomes as: cardiovascular mortality (Gehring et al, 2006), respiratory mortality and traffic intensity in a 100-m buffer (Beelen et al, 2008a), myocardial infarction (Tonne et al, 2007), cardiovascular disease (Hoffmann et al, 2006), coronary artery calcification (Hoffmann et al, 2007), cardiac function-left ventricular mass index (van Hee et al, 2009), asthma (Morgenstern et al, 2007(Morgenstern et al, , 2008Gauderman et al, 2005;McConnell et al, 2006a;Gordian, Haneuse & Wakefield, 2006;Kim et al, 2008), wheeze (McConnell et al, 2006a;Ryan et al, 2005;Venn et al, 2005;Gauderman et al, 2005;van Vliet et al, 1997), asthma hospitalization (Edwards, Walters & Griffiths, 1994;English et al, 1999;Lin et al, 2002;Wilhelm et al, 2008), lung function reduction (Sekine et al, 2004;Kan et al, 2007;Gauderman et al, 2007;Schikowski et al, 2007), birth weight (Brauer et al, 2008), childhood cancer (Savitz & Feingold, 1989;Pearson, Wachtel & Ebi, 2000), and lung cancer (Beelen et al, 2008b). Therefore, the observed excess risk in proximity to roads cannot solely be explained by socioeconomic status; although associations between traffic proximity and health impacts have been observed in locations where both high and low socioeconomic status occur in close proximity to roads (Généreux et al, 2008), its influence cannot be ruled out.…”
Section: Rationalementioning
confidence: 99%
“…Traffic density has been estimated at the county level, 5 the census block level, 44 and within selected radii (50-300 m) of a residence 10,11,30 using publically or commercially available sources or some combination thereof. The traffic density estimate may be based on only those roads for which actual traffic volume data are collected, 11,44 or traffic volumes may be assigned to neighboring roads using models or comparison to roads with similar capacities.…”
Section: Rationale For Using Surrogate Methods For Characterizing Tramentioning
confidence: 99%
“…Studies that use proximity as a surrogate for near-roadway exposures often use a dichotomous exposure variable for living inside or outside a specified buffer zone of a roadway. Buffer distances typically range between 50 and 300 m. 30,35,36,40 Traffic-level data layers were developed to include 100-and 200-m buffers measured from the edge of roadways with traffic volumes over 20,000 vehicles per day. Centerline data for the buffers were based on the MassGIS Executive Office of Transportation roads data layer.…”
Section: Traffic Exposure Assessmentmentioning
confidence: 99%
“…Exposure to traffic-related air pollution has been associated with the prevalence and exacerbation of asthma and respiratory symptoms in children (Brauer et al 2007;Gehring et al 2010;Gordian et al 2006;Kim et al 2008;McConnell et al 2006;Nordling et al 2008). …”
Section: Introductionmentioning
confidence: 99%